The use of durian seeds (Durio zibethinus Murr) as flour products from Tolitoli and Donggala Regencies - Purnama, Ningsih; Said, Irwan; Sitti Rahmawati; Dandi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Durian seeds (Durio zibethinus murr) have gotten less attention in the past. Therefore, it is necessary to treated them into culinary items like flour. The durian used in flour production was a local durian from Tolitoli and Donggala Regencies. As a result, a study was conducted to determine the quantities of carbohydrates, lipids, proteins, manganese (Mn), and zinc (Zn) in durian seeds flour. The composition of durian seeds flour from Tolitoli regency obtained was 59.2% for carbohydrate, 3.24% of lipids, 8.75% of proteins, 10.1 mg/kg of Mn, and 6.30 mg/kg of Zn. While durian seed flour from Donggala Regency obtained was 41.76% of carbohydrate, 3.24% of lipids, 10.93% of protein, 7.1 mg/kg of Mn, and 1.22 mg/kg of Zn. According to these results and the National Standardization Agency of Indonesia, durian seed flour can be used as an alternative local food ingredient to fulfil the body's demands for carbohydrates, lipids, proteins, manganese, and zinc. Furthermore, durian seed flour, when processed as a food ingredient, can be used as a replacement for wheat flour